1959
DOI: 10.1083/jcb.5.1.97
|View full text |Cite
|
Sign up to set email alerts
|

The Swelling of Rat Liver Mitochondria by Thyroxine and its Reversal

Abstract: The in vitro swelling action of L-thyroxine on rat liver mitochondria as examined photometrically represents an acceleration of a process which the mitochondria are already inherently capable of undergoing spontaneously, as indicated by the identical kinetic characteristics and the extent of thyroxine-induced and spontaneous swelling, the nearly identical pH dependence, and the fact that sucrose has a specific inhibitory action on both types of swelling. However, thyroxine does not appear to be a "catalyst" or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1960
1960
1994
1994

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…About half the protein of mitochondria is released in soluble form on disrupting the particles (Hogeboom & Schneider, 1950;Spector, 1953). Furthermnore, the swelling of mitochondria can be prevented or reversed by adding colloids to the medium, whereas sucrose is ineffective (Lehninger, Ray & Schneider, 1959). Therefore isolated mitochondria may tend to swell if their limiting membranes become permeable to sucrose and salts while remaining impermeable to colloids.…”
Section: Effect Of Temperature Although the Results Inmentioning
confidence: 99%
“…About half the protein of mitochondria is released in soluble form on disrupting the particles (Hogeboom & Schneider, 1950;Spector, 1953). Furthermnore, the swelling of mitochondria can be prevented or reversed by adding colloids to the medium, whereas sucrose is ineffective (Lehninger, Ray & Schneider, 1959). Therefore isolated mitochondria may tend to swell if their limiting membranes become permeable to sucrose and salts while remaining impermeable to colloids.…”
Section: Effect Of Temperature Although the Results Inmentioning
confidence: 99%
“…At this concentration of ATP, Mg2+, EDTA or bovine serum albumin did not potentiate, though at ATP concentrations less than 3-3mM Mg2+ or serum albumin+EDTA slightly enhanced the ATP-induced contraction. Lehninger (1959), in a detailed study ofthe action of ATP in causing the reversal of thyroxine-induced swelling of rat liver mitochondria, observed that sucrose added to the basal tris-potassium chloride medium inhibited the swelling and ATP reversal, suggesting a common denominator in these two events. Fig.…”
Section: O 10mentioning
confidence: 99%
“…Measurement of swelling of the mitochondria with absorbance at 520 mg The swelling of the mitochondria in the course of aging in 0.25 M sucrose (pH 7.4) at 4°C was measured by absorbance changes at 520 mg using Beckman model DU spectrophotometer every 24 hours until 20 days. The stock suspension was diluted with 0.25 M sucrose (pH 7.4) to yield an initial absorbance between 0.80 and 1.00 (10). Fig.…”
Section: Preparation Of Electron Microscopy-fixation Embedding and Smentioning
confidence: 99%